Annual Report of the Economic and Social Commission for Asia and the Pacific 2008 - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2013)
The Annual Report chronicles the United Nations Economic and Social Commission for Asia and the Pacific’s achievements and future goals, against a backdrop of major global shifts sweeping across the economic, social and environmental landscape. UNESCAP promotes rigorous analysis and peer learning through its seven core areas of work: macroeconomic policy and development, trade and investment, social development, transport, statistics, environment and development, information communications technology and disaster risk reduction. This report is essential reading for anyone interested in the Asia-Pacific region.